The Alzheimer's Disease Centers' Uniform Data Set (UDS): the neuropsychologic test battery - Weintraub, Sandra; Salmon, David; Mercaldo, Nathaniel; Ferris, Steven; Graff-Radford, Neill R; Chui, Helena; Cummings, Jeffrey; DeCarli, Charles; Foster, Norman L; Galasko, Douglas; Peskind, Elaine; Dietrich, Woodrow; et al. (Alzheimer disease and associated disorders, 2009)
The neuropsychologic test battery from the Uniform Data Set (UDS) of the Alzheimer's Disease Centers (ADC) program of the National Institute on Aging consists of brief measures of attention, processing speed, executive function, episodic memory, and language. This paper describes development of the battery and preliminary data from the initial UDS evaluation of 3268 clinically cognitively normal men and women collected over the first 24 months of utilization. The subjects represent a sample of community-dwelling, individuals who volunteer for studies of cognitive aging. Subjects were considered "clinically cognitively normal" based on clinical assessment, including the Clinical Dementia Rating scale and the Functional Assessment Questionnaire. The results demonstrate performance on tests sensitive to cognitive aging and to the early stages of Alzheimer disease in a relatively well-educated sample. Regression models investigating the impact of age, education, and sex on test scores indicate that these variables will need to be incorporated in subsequent normative studies. Future plans include: (1) determining the psychometric properties of the battery; (2) establishing normative data, including norms for different ethnic minority groups; and (3) conducting longitudinal studies on cognitively normal subjects, individuals with mild cognitive impairment, and individuals with Alzheimer disease and other forms of dementia.